EFFECT OF FIRM CHARACTERISTICS ON FINANCIAL PERFORMANCE OF LISTED INDUSTRIAL FIRMS IN NIGERIA - Amoge Eneh, Catherine (African Journal of Social and Behavioural Sciences, 2026)
This study examined the effect of firm characteristics on the financial performance of listed industrial firms in Nigeria, covering a ten-year period from 2015 to 2024. The study specifically investigated the influence of firm size, firm age, and leverage on financial performance, measured by return on assets (ROA). The population comprised all industrial firms listed on the Nigerian Exchange Group, while a purposive sampling technique was employed to select five firms: Berger Paints Plc, Beta Cement Plc, Dangote Cement Plc, Lafarge Africa Plc, and Premier Paints Plc. Secondary data were obtained from the annual reports of the sampled firms, and an ex-post facto research design was adopted. Data analysis was carried out using descriptive statistics and Pooled Ordinary Least Squares (OLS) regression technique. The results revealed that firm size has a positive but statistically insignificant effect on ROA, while firm age and leverage have statistically significant negative effects on ROA. The study concluded that although larger firm size may enhance performance, excessive firm age and high leverage levels tend to reduce profitability. It was recommended that industrial firms adopt efficient capital structure management practices and maintain operational flexibility to sustain financial performance over time.